(untitled) (Research, Society and Development, 2021)
This paper presents the results of a laboratory study of the properties of concrete with partial substitution of recycled coarse aggregate concrete and incorporating mineral additions, silica fume and metakaolin, commercially available in the region. The tests were compressive strength and modulus of elasticity in age of 28 days. The results showed that the silica fume addition improves the properties of concrete to the residue. Silica fume filled the voids present in the aggregate, the microstructure densifies of this composite. The regards the addition of metakaolin, although the results were satisfactory, there were no statistical variability when it was compared to concrete without the addition. It is believed that this material would be more efficient at older ages. It can be concluded that the characteristics found by the concrete with partial substitution of 50% recycled coarse aggregate concrete and adding silica techniques have potential for use in structural elements function.